Shiite activity through their online channels - Yousef A. Baker, El-Ebiary; Mohammed Elsayed Mohammed, MohammedAbdou; Mohammed Ebrahim, El Sherbiny Sakr (2020)
Allah sent His messengers to reform people with a pure belief monotheism, some of people believed in them and some of them disbelieved. Moreover, some of them stray from the true way of divine religion, diverged from, and made changes in it. All praises to Allah who has honored this Islamic nation with a blessing that was not for other nations, and it is a blessing to complete the religion and protect it from distortion and alteration until the Day of Resurrection, as almighty said. Since the spread of the Islamic missionary call, many people have tried to challenge and question it even they accused the Messenger of Allah Muhammad - may God’s prayers and peace be upon him - of lying, witchcraft and other false and shameful accusations. Among the groups and sections that drifted away from the correct approach, challenged and questioned the followers of Islam are “Shiites” who had used various means - including the Internet - to spread its deviations related to belief and law among the Sunnis, so we have to highlight some of these deviations and their criticality. There is no doubt that the means of modern technology today are essential institutions that have beaten all other institutions. Through it, you can broadcast the beliefs and ideas whatever you intend to. Shiites have exploited this medium and have published many private and public pages on the Internet. Shiites were keen to distort the image of the Sunnis among the societies. Therefore, thought the topic of the research should be Shiite activity through their online channels.